A Molecular Mechanism of Ethanol Dependence: The Influence of the Ionotropic Glutamate Receptor Activated by N-Methyl-D-Aspartate - Cordero, Sonia Luz Albarracín; II, Bernd Robert Stab; Guillen, Felipe; Montano, Edgar Antonio Reyes (IntechOpen, 2012)
None